Benzene conversion using a partial combustion approach in a packed bed reactor. (15th January 2022) - Ahmad, Waqar; Lin, Leteng; Strand, Michael
Abstract: This study investigates the partial combustion technique for tar conversion using a modified experimental set up comprising a packed bed reactor with bed-inside probe for air supply. Simulated producer gas (SPG) and benzene were selected as a real producer gas alternative and model tar component respectively. The benzene conversion was investigated under different experimental conditions such as reactor temperature (650–900 °C), packed bed height (0–12 cm), residence time (1.2–1.9 s), air fuel ratio (0.2 and 0.3) and SPG composition. The results showed insignificant effect of temperature over benzene conversion while air fuel ratio of 0.3 caused high benzene conversion than at 0.2. Absence of packed bed lead high benzene conversion of 90% to polyaromatic hydrocarbons (PAHs) compared to similar low PAHs free benzene conversion of 32% achieved at both packed heights. In SPG composition effect, H2 and CH4 had a substantial inverse effect on benzene conversion. An increase in H2 concentration from 12 to 24 vol% increased the benzene conversion from 26 to 45% while an increase in CH4 concentration from 7 to 14 vol% reduced the benzene conversion from 28 to 4%. However, other SPG components had insignificant impacts on benzene conversion. Highlights: Examining the impact of integrated packed bed assembly on benzene conversion. Impact of experimental conditions and SPG composition on benzene conversion. No significant effect of temperature and packed bed heights on benzene conversion. Positive impact of air/fuel ratio on benzene conversion. Substantial inverse effects of H2 and CH4 on benzene conversion.